PENGARUH PENERAPAN MEDIA PEMBELAJARAN BERBASIS ELEKTRONIK TERHADAP HASIL BELAJAR EKONOMI BISNIS KELAS X BISNIS MANAJEMEN SMK SWASTA AR RAHMAN MEDAN TAHUN PELAJARAN 2021/2022 - Melisa Melisa; Zulkifli Hasibuan (Jurnal Inovasi Penelitian, 2022)
This study aims to determine the effect of the application of electronic-based learning media on the learning outcomes of business economics class X SMK Swatsta Ar-Rahman Medan. This type of research uses experimental research using a quantitative approach with a quasi-experimental method with a non-equivalent control group design pattern (non-equivalent pretest-posttest). The sample used consisted of 2 populations as the experimental class and the control class so that the 2 populations were tested for normality and homogeneity. Data collection techniques used are observation and documentation. The research instrument consisted of 30 questions, so the instrument was tested using validity and reliability tests. The data analysis technique used is data reduction, data presentation to find the average and hypothesis test t. From the results of the hypothesis test stating tcount> ttable, with the acquisition of 1.8820> 1.7074, the results of the t-test prove that Ha is accepted and H0 is rejected. The results show that by applying electronic-based learning media it can be proven to improve students' business economics learning outcomes at the Ar-Rahman Private Vocational School Medan.